Prokineticin 2 regulates the electrical activity of rat suprachiasmatic nuclei neurons. - Ping Ren; Huiping Zhang; Fang Qiu; Yu-Qiang Liu; Huaiyu Gu; Diane K O'Dowd; Qun-Yong Zhou; Wang-Ping Hu (PLoS ONE, 2011)
Neuropeptide signaling plays roles in coordinating cellular activities and maintaining robust oscillations within the mammalian suprachiasmatic nucleus (SCN). Prokineticin2 (PK2) is a signaling molecule from the SCN and involves in the generation of circadian locomotor activity. Prokineticin receptor 2 (PKR2), a receptor for PK2, has been shown to be expressed in the SCN. However, very little is known about the cellular action of PK2 within the SCN. In the present study, we investigated the effect of PK2 on spontaneous firing and miniature inhibitory postsynaptic currents (mIPSCs) using whole cell patch-clamp recording in the SCN slices. PK2 dose-dependently increased spontaneous firing rates in most neurons from the dorsal SCN. PK2 acted postsynaptically to reduce γ-aminobutyric acid (GABA)-ergic function within the SCN, and PK2 reduced the amplitude but not frequency of mIPSCs. Furthermore, PK2 also suppressed exogenous GABA-induced currents. And the inhibitory effect of PK2 required PKC activation in the postsynaptic cells. Our data suggest that PK2 could alter cellular activities within the SCN and may influence behavioral and physiological rhythms.